Physicochemical and functional characterization of chitosan from horn snail gastropod Telescopium telescopium - Thangaraj Jebarani Rajathy, Muthukumarasamy Srinivasan, Theivasigamani Mohanraj (Journal of Applied Pharmaceutical Science, 2021)
Chitosan is a naturally occurring biopolymer having immense structural possibilities to formulate novel properties and applications especially in the field of biomedical science. In view of the above, the present findings were aimed to develop chitosan from marine gastropod Telescopium telescopium and characterize its structural, chemical, and thermal properties by means of Fourier Transform Infrared Spectroscopy, X-ray Diffraction, Scanning Electron Microscopy and Thermogravimetric analysis. The synthesized chitosan was soluble in 1% acetic acid with a degree of deacetylation of 74.96%. The yield was estimated as 42%, with ash and moisture content of 1.2% and 3.9%, respectively, and showed binding capacities of 240% (WBC) and 280% (FBC). The synthesized chitosan exhibited good bactericidal effect towards Bacillus subtilis and Vibrio cholerae. The T. telescopium-derived chitosan also proves to be a novel, non-antibiotic agent preventing biofilm formation.
Keywords: Biopolymer, biofilm, chitosan, thermogravimetric, Telescopium telescopium.